1988
DOI: 10.1002/neu.480190502
|View full text |Cite
|
Sign up to set email alerts
|

Activity sharpens the regenerating retinotectal projection in goldfish: Sensitive period for strobe illumination and lack of effect on synaptogenesis and on ganglion cell receptive field properties

Abstract: The regenerating optic nerve of goldfish first reestablishes a rough retinotopic map on the contralateral tectum and then sharpens it. Disruption of visual activity, either by blocking activity with intraocular tetrodotoxin (TTX; Schmidt and Edwards, 1983) or by synchronizing activity with strobe illumination (Schmidt and Eisele, 1985), disrupts the sharpening process: the map is correctly oriented but the multiunit receptive fields at each point average 25-40 degrees in diameter. In order to test whether stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
28
0

Year Published

1990
1990
2006
2006

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 44 publications
8
28
0
Order By: Relevance
“…Regenerating optic axons initially arrive at the optic tectum as early as 14 days after optic nerve crush . Because the peak of GFMLCKl mRNA expression occurred before this time, we concluded that this upregulation more closely coincided with the pe- nod of active axonal outgrowth (Schmidt et al, 1983 ) rather than with that of synaptogenesis or retinotopic map sharpening (Eisele and Schmidt, 1988). This correlation is consistent with GFMLCKl as the source of the MLCK activity that was previously shown by pharmacological inhibitors to be essential for growth cone motility (Jian et al, 1994).…”
Section: Increased Gfmlckl Expression During Axonal Outgrowth In Retisupporting
confidence: 69%
See 2 more Smart Citations
“…Regenerating optic axons initially arrive at the optic tectum as early as 14 days after optic nerve crush . Because the peak of GFMLCKl mRNA expression occurred before this time, we concluded that this upregulation more closely coincided with the pe- nod of active axonal outgrowth (Schmidt et al, 1983 ) rather than with that of synaptogenesis or retinotopic map sharpening (Eisele and Schmidt, 1988). This correlation is consistent with GFMLCKl as the source of the MLCK activity that was previously shown by pharmacological inhibitors to be essential for growth cone motility (Jian et al, 1994).…”
Section: Increased Gfmlckl Expression During Axonal Outgrowth In Retisupporting
confidence: 69%
“…In fish of this size kept at 20°C, the first fibers reach the rostral edge of the tectum at around 14 days and synapse formation is first detectable electrophysiologicall y in extreme rostral tectum around 20 days (Schmidt et al, 1983). Retinotopic map sharpening also occurs later, ensuing after synaptogenesis (Eisele and Schmidt, 1988), and GFMLCK 1 expression greatly subsides before either is underway. Thus, there is a good correlation of high MLCK expression with the period of axon elongation.…”
Section: Consistent With a Role In Neurite Outgrowthmentioning
confidence: 96%
See 1 more Smart Citation
“…Normal arbors were very planar and stratified, with the fine caliber the most superficial, the coarse next deeper, and the medium the deepest. Mature, regenerated arbors (examined at 6 months postcrush) reestablished these same three classes of arbors and calibers of axons (Schmidt et al, 1988). The sizes were approximately the same, and they had roughly the same number and order of branch endings and terminated at roughly the same class-specific depths although they were not as well stratified (Schmidt et al, 1988).…”
Section: Control-regenerated Arborsmentioning
confidence: 95%
“…In a previous report (Schmidt et al, 1988), we found that optic arbors in tectum could be divided into three classes according to the caliber of axon from which they arose (Fig. 1 ).…”
Section: Control-regenerated Arborsmentioning
confidence: 96%